The Influence of Stakeholder Power on Environmental Performance and Its Impact on Environmental Disclosure - Darmawati, Deni; Yulia Eka Riyanti; Nadia Putri (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2023)
The aims of this study are to examine the effect of Stakeholder Power on Environmental Performance and its impact on Environmental Disclosure. The stakeholder power in this research is more complete than some previous research (Testa et al., 2018; Wang et al., 2020) that are auditor power, government power, creditors power and shareholder power. This study uses sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2020. Using purposive sampling method, the sample were 34 companies that produced observations of 136 firm years. The data analysis used in this research is multiple linear regression analysis. The results of this study show that Auditors Power and Government Power have a positive effect on Environmental Performance. Meanwhile, Creditors Power and Shareholders Power have no effect on Environmental Performance. This study also found that Environmental Performance had a positive effect on Environmental Disclosure. This study integrated the researches that investigated the effect of stakeholder power on environmental performance and researches that investigated the effect of environmental performance on environmental disclosure. The integration of the two research topics will provide a complete picture of the role of stakeholders in improving environmental performance and their impact on environmental disclosure.